2002
DOI: 10.1136/jech.56.11.876
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of body mass index of an urban adult population in western India

Abstract: Study objective: To describe height, weight, and body mass index (BMI) of the adult urban population in Mumbai, western India and to estimate the prevalence and severity of thinness and overweight in this population. To describe the association of BMI with education, age, and tobacco habits in an urban Indian population. Design: Cross sectional representative survey of 99 598 adults (40 071 men and 59 527 women). Setting: The survey was carried out in the city of Mumbai (formerly known as Bombay) in western In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
103
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 12 publications
13
103
1
Order By: Relevance
“…Details of methodology have been reported. 5 Voters' lists were used to enrol the subjects and the survey was confined to the main city-population density of 48 830 inhabitants/km 2 , from population of 3.42 million in an area of about 70 km 2 . All individuals aged 35 years and over were approached by investigators for interview and BP measurements.…”
mentioning
confidence: 99%
“…Details of methodology have been reported. 5 Voters' lists were used to enrol the subjects and the survey was confined to the main city-population density of 48 830 inhabitants/km 2 , from population of 3.42 million in an area of about 70 km 2 . All individuals aged 35 years and over were approached by investigators for interview and BP measurements.…”
mentioning
confidence: 99%
“…In developed countries, for instance in the United States, overweight and obesity disproportionately impact those having low incomes, having low education levels, and belonging to minority race/ ethnicity (Drewnowski and Specter, 2004;USDHHS, 2001;Mokdad et al, 2003). In developing countries, such as India, nutritional status is related to levels of education, standard of living, and social status such that undernutrition is associated with low individual socioeconomic status (SES) and overnutrition is associated with high SES (Shukla et al, 2002;Griffiths and Bentley, 2005;Osmani and Sen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast the prevalence of underweight among Indian male and female elderly was much higher than these figures. Shukla et al (9) in their study on urban Indian adults found that 24-36% and 24-48% of males and females aged 65years and above were underweight. In a recent study it has been reported that 11% of healthy elderly Pakistani men are underweight (18).With respect to the prevalence of overweight and obesity, strict comparisons across Asian studies are not possible due the differences in BMI cut-offs that have been used to define these two entities.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in many developing countries there is a double burden of malnutrition; a high prevalence of both underweight and overweight/obesity (9). In order to determine whether a similar situation exists among the Sri Lankan elderly, it is necessary to obtain information about the distribution of BMI in this group.…”
Section: Introductionmentioning
confidence: 99%